Communication between deep sea container terminals and hinterland stakeholders: information needs and the relevance of information exchange. Issue 4 (December 2018) - Wiegmans, Bart; Menger, Isle; Behdani, Behzad; Arem, Bart
Abstract Hinterland container transport is increasingly identified as an important element in door-to-door transportation of goods in the context of global supply chains. Container terminal operators also continuously seek strategies to distinguish themselves from their competitors by providing dedicated information on containers, transport means and the terminal. This paper explores the information needs of container terminals and hinterland stakeholders and highlights the importance of different information types for different stakeholders. Information needs are studied through gate survey, interviews and questionnaires sent to different parties involved in seaport-hinterland transportation at the APM Terminal in Rotterdam. This information is divided in three main categories: information about containers, information about transport means and information about deep sea terminal. In each category, the specific information types and the importance of that information for each hinterland party are discussed. The findings of this research can be used by different hinterland parties to optimize the planning and control of container logistics processes. They can also support developing customized ICT solutions for hinterland transportation.